Tokyo ESP. 6 - Segawa, Hajime (Vertical, Inc, 2016)
"The battle in Hong Kong's black market tournament culminates with Rinka facing off with someone very close to the big bad boss... and Rinka winds up having to face some harsh truths about the choices she has made up until this point. Meanwhile, Kobushi makes a decision about her path in the criminal world with potentially fatal consequences. Back in Tokyo, Ren had expected life at the ESP Academy to return to normal, except a certain student has gone missing, and another classmate finds herself swept up by the immense aura of a new evil presence that has set foot in metropolis..."Back cover.